KEWENANGAN PEMERINTAH DAERAH DALAM PENGADAAN TANAH BAGI PELAKSANAAN PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Dikson Kristian; I Nyoman Suyatna; Cokorda Dalem Dahana (Kertha Negara : Journal Ilmu Hukum, 2014)
Government Authority in the implementation of land acquisition for the constructionof a public interest in the Government authorities to provide land for the construction of thepublic interest . The problem that arises then is unclear rules governing the authority of theGovernment in the implementation of land acquisition for the construction of the publicinterest as well as legal protection for land rights holders affected by the land acquisition bythe government. This journal normative method to approach the study of literature. In Article6 of Law No. 12 The year 2012 is mentioned land acquisition for public interests held by theGovernment. Section 8 of Presidential Decree. 71 The year 2012 also mentioned that theGovernor carry out a preparatory stage of land acquisition after receiving the land acquisitionplanning documents. Law No. 2 In 2012 and Presidential Decree. 71 The year 2012 is set onthe deliberations, awarding damages, and filing a lawsuit for land rights holders. It can beconcluded authority for the implementation of land acquisition for the construction of publicinterest under the authority of the Governor and the Provincial Government as the legalprotection of the rights of the owner of the land is reflected through the regulation ofdeliberation, of compensation, and the provision of opportunity to file a lawsuit to theAdministrative Court and to District Court.